The Relationship Between Social Media Addiction and Eating Disorder Tendencies - Rosdiana, Nila; Kurniawan, Lely Setyawati (Dinasti Publisher, 2025)
This study was motivated by the increasing use of social media, which not only provides benefits but also creates negative impacts on mental health, including eating disorder tendencies. The aim of this research was to examine the relationship between social media addiction and eating disorder tendencies among adolescents and young adults. A quantitative survey method was employed by distributing questionnaires to purposively selected respondents. The results revealed a significant positive correlation between social media addiction and eating disorder tendencies, indicating that individuals with higher levels of social media addiction are more likely to develop unhealthy eating behaviors such as strict dieting, binge eating, and body dissatisfaction. Gender and duration of social media use were identified as factors that reinforced this relationship. The study concludes that preventive measures through media literacy education, psychological support, and public health interventions are essential to reduce the negative impacts of excessive social media use.